Social Stigma and HIV/AIDS - Petros Ouzounakis; Aikaterini Frantzana; Christos Iliadis; Kiriaki Tachtsoglou; Vassiliki Diamantidou and Lambrini Kourkouta (Professor Despina Sapountzi-Krepia, 2024)
Social Stigma and HIV/AIDS